Functional consequences of NR2 subunit composition in single recombinant N-methyl-d-aspartate receptors - Brimecombe, Jessica C. (The National Academy of Sciences of the USA, 1997)
Single-channel recordings were obtained from Chinese hamster ovary cells transfected with the N-methyl-d-aspartate (NMDA) receptor subunit NR1 in combination with NR2A, NR2B, NR2C, or NR2A/NR2B. NMDA-activated currents were recorded under control conditions and in the presence of a thiol reductant (DTT), an oxidant (5,5′-dithio-bis[2-nitrobenzoic acid], DTNB), or the noncompetitive antagonist CP101,606 (CP). For all subunit combinations, DTT increased the frequency of channel opening when compared with DTNB. In addition, channels obtained from NR1/NR2A-transfected cells also exhibited a pronounced difference in mean open dwell-time between redox conditions. CP dramatically reduced both the open dwell-time and frequency of channel opening of NR1/NR2B-containing receptors, but only modestly inhibited NR1/NR2A and NR1/NR2C channel activity. A small number of patches obtained from cells transfected with NR1/NR2A/NR2B had channels with properties intermediate to NR1/NR2A and NR1/NR2B receptors, including insensitivity to CP block but redox properties similar to NR1/NR2B, consistent with the coassembly of NR2A with NR2B. Hence, NMDA receptors containing multiple types of NR2 subunits can have functionally distinguishable attributes.